VEGF expression in human macrophages is NF-kappaB-dependent: studies using adenoviruses expressing the endogenous NF-kappaB inhibitor IkappaBalpha and a kinase-defective form of the IkappaB kinase 2. - Kiriakidis, S; Andreakos, E; Monaco, C; Foxwell, B; Feldmann, M; Paleolog, E (2003)
Vascular endothelial growth factor (VEGF) is the most endothelial cell-specific angiogenic factor characterised to date, and it is produced by a variety of cell types. In macrophages, VEGF has been shown to be upregulated by the inflammatory mediator lipopolysaccharide (LPS) and by engagement of CD40 by CD40 ligand (CD40L). Because LPS and CD40L activate nuclear factor-kappaB (NF-kappaB) in monocytes, we investigated in this study whether VEGF production in macrophages, when stimulated with either LPS or CD40L, is NF-kappaB-dependent. We used adenoviral constructs over-expressing either IkappaBalpha (AdvIkappaBalpha), the endogenous inhibitor of NF-kappaB, or a kinase-defective mutant of IKK-2 (AdvIKK-2dn), an upstream activator of IkappaBalpha, to infect normal human monocyte-derived macrophages. We observed that LPS-induced production of VEGF in human macrophages was almost completely inhibited (>90%) following adenoviral transfer of IkappaBalpha. In addition, we observed significant inhibition of the CD40L-induced VEGF production in macrophages following infection with AdvIkappaBalpha. Expression of IKK-2dn in macrophages decreased VEGF production in response to LPS or CD40L by approximately 50%, suggesting that in addition to IKK-2, other kinases might be involved in NF-kappaB activation. These results show for the first time that VEGF production in human macrophages is NF-kappaB dependent. NF-kappaB regulates many of the genes involved in immune and inflammatory responses, and our study adds the angiogenic cytokine VEGF to the list of NF-kappaB-dependent cytokines.